An innovative method for the preservation and exhibition of four plastination specimens from a single minke whale (Balaenoptera acutorostrata) - Jiang, Wen-Bin; Song, Xue; Shah, M. Adeel Alam; Han, Jian; Ma, Xue-Wei; Sui, Hong-Jin (Frontiers in Marine Science, 2025)
Plastination represents the most advanced technique for preserving biological specimens, widely adopted in education, scientific research, and popular science. This study employed the technique of plastination to explore an innovative method for preserving and exhibiting minke whales, addressing challenges to optimize the use of rare marine mammal specimens and the multi-layered understanding of cetacean anatomy. A 6.5-meter-long adult female minke whale cadaver, weighing 3,368 kg, was dissected, plastinated with polymers, and assembled with internal support frames. Subsequently, skin, muscle, bone, and viscera specimens were prepared separately. The four specimens of the minke whale can be displayed together or individually, and their internal and external structures have been mostly well preserved, with superb surface textures and fine details. This marks the first application of plastination technique to create four distinct presentations from a single minke whale cadaver globally, which significantly conserves biological materials by maximizing the use of a single rare animal body. The innovative plastination technique not only broadens our understanding of cetacean biology but also establishes a sustainable model for preserving rare marine specimens, offering insights into the relationship between structures and functions, as well as environmental adaptations. This study will provide valuable tools for education, research, and popular science education.